ChemInform Abstract: High Performance Catalysts Prepared from Al—Cu—Fe Icosahedral Quasicrystal. Issue 49 (December 2015) - Tsai, An‐Pang; Tanabe, Toyokazu; Kameoka, Satoshi
Abstract: Review: 35 refs.